Gene flow between vicariant tree species: insights into savanna-forest evolutionary relationships - Resende-Moreira, Luciana C.; Ramos, Ana Carolina S.; Scliar, Marília O.; Silva, Reinaldo M.; Azevedo, Vânia C. R.; Ciampi, Ana Y.; Lemos-Filho, José P.; Lovato, Maria Bernadete (Tree genetics & genomes, 2017)
Studying the genetic structure of vicariant species (i.e., closely related species that occupy ecologically distinct yet adjacent habitats) can shed light on the evolution and divergence of species with different ecological requirements. A previous phylogeographic study identified chloroplast DNA haplotype sharing between two vicariant tree species, one from forest ( Hymenaea courbaril ) and one from savanna ( H. stigonocarpa ) habitats. These species co-occur in the Brazilian Cerrado, a biome that encompasses forest patches and riverine forests within a savanna matrix. In order to investigate the evolutionary processes involved in the genetic divergence of these trees, we used nuclear microsatellite markers, statistical methods including approximate Bayesian computation (ABC), and leaf morphology to analyze neighboring and distant populations. Bayesian analysis revealed admixture between the species. ABC analysis supported the scenarios with the occurrence of gene flow between species during the Last Glacial Maximum or from the Holocene to the present, when compared to alternative scenarios of no gene flow or constant gene flow since divergence. However, putative hybrids did not exhibit intermediate leaflet morphology, which could be related to distinct selective pressures maintaining species integrity even in the face of gene flow. Our results suggest that despite morphological differences between savanna and forest species, interspecific barriers to gene flow might not be fully developed between vicariant tree species and that interspecific hybridization in trees from Cerrado biome may be an underdiagnosed process.